Analisis Regresi Sifat Tanah Terhadap Rebound Tiang Pancang - Amalia, Nadya; Rokhmat, Mamat; Sutisna, Sutisna; Viridi, Sparisoma; Abdullah, Mikrajuddin (Institut Teknologi Bandung, 2017)
The behavior of soil around driven pile during pile driving process directly affect the driving process. Two categories of stress are produced during the driving process, i.e. stress along the pile shaft (shear stress) and stress at the end of the pile (compression stress). Since soil is a porous medium, shear and compressive stresses during the driving process will force water to come out of the pores in the soil. Related to hammering and low permeability of the soil at rebound zones such as clay, water can not flow out of the pores and can not be dissipated instantly. As a result, a high pore water pressure will be generated along the shaft and at the end of the pile. Pile coating with titanium dioxide (TiO2) is able to make the pile to be driven deeper than pile without coating with the same count of hammer strokes for pile driving in clay soils. Uniquely, the coating does not give effect to the pile driving in non-cohesive soils. This indicates that the coating is capable in minimizing pile rebound. Regression model is used in this study to identify the characteristics of engineering soil parameters which may cause the rebound phenomenon.